Preparation and application of oxyhydroxide and alloy supported catalyst
The preparation of hydroxyoxide and alloy-supported catalysts with controllable atomic lattice strains through electrodeposition method solves the problems of slow kinetics and expensive precious metal catalysts in electrocatalytic water cracking, and achieves efficient and stable electrocatalytic performance.
Patent Information
- Application Number
- CN202510523035.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2025-07-18
AI Technical Summary
The existing electrocatalytic water cracking technology has problems with slow kinetics, short operating life and expensive precious metal catalysts, and the lattice strain research of inorganic transition metal compounds is difficult to characterize, and the relationship between electronic structure-binding energy-electrochemical properties is not clear enough.
The hydroxyoxide and alloy-supported catalyst with controllable atomic-scale lattice strain were prepared by environmentally friendly electrodeposition method. A three-dimensional hierarchical branch and leaf structure was adopted, and an alloy branch and leaf structure was formed on the foam copper support using an electrodeposition precursor, which improved the specific surface area of the catalyst and electron transport efficiency.
Efficient and stable electrocatalytic hydrogen and oxygen evolution reactions are achieved, and the catalyst has good application prospects, simplifying the preparation process and reducing costs.
Smart Images

Figure CN120330787A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalyst preparation, and particularly relates to the preparation and application of a hydroxyoxide and alloy supported catalyst, and more particularly to a highly efficient hydroxyoxide and alloy supported catalyst with controllable atomic-level lattice strain. Background Art
[0002] With the continuous increase in the demand and consumption of traditional energy sources, various environmental problems have become increasingly serious. Sustainable hydrogen energy and its feasible storage and conversion technologies can effectively reduce the dependence on fossil fuels. Electrochemical water splitting is one of the most promising technologies for producing high-purity hydrogen, which has the potential to solve the dilemmas faced by energy and environmental problems. It mainly includes two key electrochemical reactions, the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. Unfortunately, there are often three basic obstacles in the process of electrochemical water splitting: slow kinetics, short operating life, and expensive noble metal catalysts. Therefore, there is an urgent need to rationally design and develop composite electrocatalysts with high efficiency, high durability, and low cost.
[0003] The electronic structure has been identified as an important descriptor for explaining the corresponding catalytic behavior, because the conductivity and adsorption strength of the intermediate (equivalent to the reaction barrier) are two main behaviors of the electronic structure, which directly determine the reaction kinetics. Among them, lattice strain engineering can manipulate the electronic structure by directly changing the atomic spacing, thereby regulating the binding energy between the electrocatalyst and the reaction intermediate, and is considered an advantageous means for improving catalytic activity. However, most of the research related to strain engineering has focused on noble metal-based catalysts, and the research on the lattice strain of inorganic transition metal compounds is still rare due to their complex structures and difficulty in characterization. The relationship between the electronic structure-binding energy-electrochemical properties is not clear enough, and the research scope is also limited. Moreover, even the creation of ordinary heterostructures and lattice strain engineering involves cumbersome multi-step synthesis processes and is difficult to control.
[0004] The present invention has successfully prepared a highly efficient hydroxyoxide and alloy supported catalyst with controllable atomic-level lattice strain through an environmentally friendly method. The catalyst has a three-dimensional hierarchical foliage structure. Among them, the leaf structure is beneficial to increasing the specific surface area and the exposure of surface active sites, and improving the mass transfer efficiency of molecules; in addition, the interconnected network of the branch structure is beneficial to accelerating electron transfer, improving catalytic activity while providing a supporting force to enhance stability, realizing the coexistence of high activity and high stability of the catalyst. More importantly, this method is simple and easy to control, and only needs to add a new electrodeposition precursor for continuous electrodeposition. It is a sustainable catalyst synthesis method, and the prepared catalyst has excellent performance and good application prospects in electrocatalysis. Summary of the Invention
[0005] The object of the present invention is to provide a preparation method and application of a hydroxyoxide and alloy-supported catalyst in view of the problems existing in the prior art. The technical solution of the present invention is to successfully prepare a hydroxyoxide and alloy-supported catalyst with adjustable lattice strain through an environmentally friendly electrodeposition method.
[0006] The object of the present invention can be achieved through the following solutions: The present invention provides a preparation method of a hydroxyoxide and alloy-supported catalyst, comprising the following steps: S1. Dissolve an ammonium salt in an alkaline solution to obtain a mixed solution; then immerse copper foam in the mixed solution, heat it to 50-120 °C, and perform an in-situ oxidation reaction to obtain a nanoarray copper oxide support; S2. Mix and dissolve a transition metal salt (precursor), a copper salt and an ammonium salt to obtain an electrodeposition mixed solution; S3. Immerse the obtained nanoarray copper oxide support as a working electrode in the electrodeposition mixed solution for electrodeposition to obtain a hydroxyoxide and alloy-supported catalyst (transition metal catalyst).
[0007] As an embodiment of the present invention, in step S1, the ammonium salt includes one or more of ammonium persulfate, ammonium chloride, ammonium bicarbonate, and ammonium nitrate. The molar concentration of the ammonium salt in the mixed solution is 0.001-0.4 M, preferably 0.01-0.2 M, and more preferably 0.05-0.2 M.
[0008] As an embodiment of the present invention, in step S1, the alkaline solution includes one or more of sodium hydroxide solution, potassium hydroxide solution, and ammonia water solution. The molar concentration of the base in the mixed solution is 0.025-5 M, preferably 0.25-5 M, and more preferably 1-5 M.
[0009] As an embodiment of the present invention, in step S1, the heating temperature is 70-90 °C.
[0010] As an embodiment of the present invention, in step S1, the time of the in-situ oxidation reaction is 5-60 min, preferably 20-60 min. At the same salt concentration, as the time becomes longer, the array width becomes thinner and longer (grows upward), but it will not extend infinitely. After 20-30 min, the growth change is not significant. Within 60 min, the change trend of the concentration effect is much greater than that of the time effect.
[0011] As an embodiment of the present invention, in step S1, the surface of the obtained nanoarray copper oxide support has a CuO array with a width of 0.05-2 µm, preferably 0.05-1 µm.
[0012] The copper oxide support of the present invention is subjected to oxidation treatment at a certain temperature (50 - 120 °C), and a support with a copper oxide array on the surface can be directly obtained. By controlling the salt concentration (the higher the concentration, the finer the array; if the concentration is too high, the array will tend to re - fuse), a copper oxide array with an appropriate array width can be directly formed. The copper oxide array is beneficial to the deposition of the catalyst, beneficial to the formation of the branch - leaf structure, and has a larger specific surface area and more surface active sites. Without heating for oxidation treatment, a support with copper hydroxide on the surface is usually obtained. After calcination, a copper oxide support is obtained, but the surface copper oxide obtained does not have an array structure, showing a rod - shaped, fluffy, porous structure, and is unstable, easily collapsing during subsequent catalyst deposition or use, affecting the morphology of the catalyst. The two - dimensional array copper oxide on the surface obtained by the present invention is more stable.
[0013] As an embodiment of the present invention, in step S2, the transition metal salt (precursor) includes sulfate; the transition metal includes one or more of nickel, cobalt, iron, and manganese.
[0014] As an embodiment of the present invention, in step S2, the copper salt includes one of copper sulfate and copper chloride. Preferably, it is copper sulfate, which is the same salt as the transition metal salt.
[0015] As an embodiment of the present invention, in step S2, the proportion of the copper salt in the total molar amount of the transition metal salt (precursor) and the copper salt is 20 - 60%, preferably 20 - 50%, and more preferably 20 - 40%. The ratio between the two can be changed (1:1, 4:3, 4:2, 3:4, 3:2, 2:4, 2:3). In the electrodeposition mixture, the total molar concentration of the transition metal salt (precursor) and the copper salt is 1 - 100 mM, preferably 40 - 60 mM.
[0016] The content of the copper salt in the deposition mixture of this application is relatively high. Copper is mainly used to form branches, and the hydroxy - oxide of the surface transition metal forms leaves. The branches formed by copper can provide support to enhance stability. If the copper content is low, copper and the transition metal will form a dendritic catalyst, and the stability is not good.
[0017] As an embodiment of the present invention, in step S2, the ammonium salt includes one or more of ammonium sulfate, ammonium chloride, ammonium bicarbonate, and ammonium nitrate. In the electrodeposition mixture, the concentration of the ammonium salt is 0.05 - 0.5 g / 100 mL, preferably 0.3 - 0.4 g / 100 mL.
[0018] As an embodiment of the present invention, in step S3, during electrodeposition, the ambient temperature is 20 - 30 °C, and the ambient pressure is 0.1 - 1 MPa.
[0019] As an embodiment of the present invention, in step S3, the cathode constant current range is -0.05 A to -0.2 A, and the deposition time is 300 to 1200 s.
[0020] As an embodiment of the present invention, in step S3, during electro-deposition, a graphite rod is used as the counter electrode, the working electrode is the deposition substrate, and the reference electrode is an Ag / AgCl electrode, and electro-deposition is carried out in a cathode constant current mode.
[0021] As an embodiment of the present invention, in step S3, after the electro-deposited transition metal catalyst is collected and washed clean with deionized water, a hydroxyl oxide and alloy-supported catalyst with controllable lattice strain is obtained.
[0022] The catalyst of the present invention has a unique three-dimensional hierarchical branch-leaf structure, which includes an alloy (Cu and transition metal) branch structure and a hydroxyl oxide leaf structure. The size of the branch structure is 50 - 300 nm, and the average thickness of the leaf structure is 1.4 - 1.6 nm. The branch-leaf structure is beneficial to increasing the specific surface area and the exposure of surface active sites, improving the molecular mass transfer efficiency; in addition, the interconnected network is beneficial to accelerating electron transport, improving the catalytic activity while providing a supporting force to enhance stability. Through precise lattice strain regulation, the surface catalytic ability can be further enhanced, achieving the coexistence of high activity and high stability of the catalyst.
[0023] The hydroxyl oxide and alloy-supported catalyst is: M1OOH / M1 0 M2 0 , where M1 is a trivalent metal, M1 0 M2 0 is a zero-valent metal.
[0024] The present invention also provides the application of the hydroxyl oxide and alloy-supported catalyst obtained by the preparation method in electrocatalytic overall water splitting for hydrogen evolution and oxygen evolution.
[0025] The beneficial effects of the present invention are as follows: (1) The purpose of preparing a hydroxyl oxide and alloy-supported catalyst with controllable lattice strain and electrocatalytic hydrogen evolution and oxygen evolution is achieved; (2) In the hydroxyl oxide and alloy-supported catalyst with controllable lattice strain, it has a three-dimensional hierarchical branch-leaf structure. The leaf structure is beneficial to increasing the specific surface area and the exposure of surface active sites, improving the molecular mass transfer efficiency. The interconnected network of the branch structure is beneficial to accelerating electron transport, improving the catalytic activity while providing a supporting force to enhance stability, achieving the coexistence of high activity and high stability of the catalyst; (3) The electrodeposition preparation method proposed by the present invention is simple and easy to control, and can realize the preparation of hydroxyoxide and alloy-supported catalysts with controllable lattice strain in a short time. Only by adding a new electrodeposition precursor can continuous electrodeposition be carried out. It is an environmentally friendly catalyst synthesis method. The prepared catalyst has excellent performance and has good application prospects in electrocatalytic hydrogen evolution and oxygen evolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] By reading the following detailed description of the non-limiting embodiments with reference to the accompanying drawings, other features, objects, and advantages of the present invention will become more apparent: Figure 1 SEM images of x%NiOOH / NiCu hydroxyoxides and alloy-supported catalysts with different lattice strain degrees (scale bar is 2 μm), corresponding to the catalysts of Examples 1-5 (x is the lattice strain ratio); Figure 2 HRTEM images of x%NiOOH / NiCu hydroxyoxides and alloy-supported catalysts with different lattice strain degrees (scale bar is 2 μm), corresponding to the catalysts of Examples 1-5 (x is the proportion of lattice strain); Figure 3 HER polarization curves of x%NiOOH / NiCu hydroxyoxides and alloy-supported catalysts with different lattice strain degrees, corresponding to the catalysts of Examples 1-5; Figure 4 OER polarization curves of x%NiOOH / NiCu hydroxyoxides and alloy-supported catalysts with different lattice strain degrees, corresponding to the catalysts of Examples 1-5; Figure 5 SEM images of hydroxyoxides and alloy-supported catalysts Ni x Cu 5-x obtained by electrodeposition from transition metal salt (precursor) solutions with different ratios (scale bar is 2 μm); Figure 6 HER polarization curves of hydroxyoxides and alloy-supported catalysts Ni x Cu 5-x obtained by electrodeposition from transition metal salt (precursor) solutions with different ratios; Figure 7 OER polarization curves of hydroxyoxides and alloy-supported catalysts Ni x Cu 5-x obtained by electrodeposition from transition metal salt (precursor) solutions with different ratios.
[0027] Figure 8 Morphologies of CuO arrays obtained at different ammonium salt concentrations (scale bar is 2 μm); Figure 9 SEM image of the catalyst obtained in Comparative Example 6 (scale bar: 500 nm); Figure 10 OER polarization curve of the catalyst obtained in Comparative Example 6; Figure 11 HER polarization curve of the catalyst obtained in Comparative Example 6. Detailed implementation manners
[0028] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, providing detailed implementation manners and specific operation processes, which will help those skilled in the art to further understand the present invention. It should be noted that the protection scope of the present invention is not limited to the following embodiments. Several adjustments and improvements made on the premise of the concept of the present invention all belong to the protection scope of the present invention.
[0029] The present invention belongs to the technical field of electrocatalyst preparation, and relates to the preparation and application of a highly efficient hydroxyoxide and alloy-supported catalyst with controllable atomic-level lattice strain. The hydroxyoxide and alloy-supported catalyst with controllable atomic-level lattice strain is mainly prepared by the following steps: 1) Immerse a piece of foam metal in an alkaline solution containing an ammonium salt for in-situ oxidation for a certain time to prepare an oxide support; 2) Immerse the oxide support obtained in 1) in a standard three-electrode electrochemical cell containing a mixed electrolyte of a metal salt (precursor) and an ammonium salt, and perform electrodeposition by means of a constant cathode current to obtain a hydroxyoxide and alloy-supported catalyst with controllable atomic-level lattice strain. The hydroxyoxide and alloy-supported catalyst with controllable atomic-level lattice strain prepared by the present invention has a three-dimensional hierarchical branch structure. At the microscale, the branch morphology provides support and effective chemical and electron transport through a fractal network; at the atomic scale, the adjustable lattice strain improves the active sites and optimizes the catalytic reaction. This structure not only facilitates the exposure of more active sites and increases molecular mass transfer during the reaction, but also obtains strong stability through efficient electron transport through excellent network channels, thereby greatly improving the high-efficiency and stable catalytic ability of the catalyst under complex conditions. The preparation method of the present invention is simple and only needs to add a new electrodeposition precursor for continuous electrodeposition. It is an environmentally friendly catalyst synthesis method. The prepared catalyst has excellent performance and has good application prospects in electrocatalytic water splitting for hydrogen evolution and oxygen evolution.
[0030] Example 1: Dissolve 3 mmol of nickel sulfate hexahydrate, 2 mmol of copper sulfate pentahydrate and 0.35 g of ammonium sulfate in 100 mL of deionized water, and mix well to obtain an electrodeposition mixture; (2) Carry out a 20-minute room-temperature in-situ oxidation reaction on a piece of foam copper in air to obtain a CuO0 support (without a nanoarray); (3) The CuO support oxidized in-situ with air was immersed in the electrodeposition mixed solution obtained in (1). The counter electrode was a graphite rod, the working electrode was the support, and the reference electrode was an Ag / AgCl electrode. Electrodeposition was carried out at a constant cathodic current of -0.2 A for 900 s. (4) The transition metal catalyst after electrodeposition was collected and washed clean with deionized water to obtain 0% NiOOH / NiCu catalyst.
[0031] (5) The prepared 0% NiOOH / NiCu catalyst was electrocatalytically tested for HER and OER in the presence of 1 M KOH to measure its activity, and it was found that the HER and OER overpotentials at 10 mA cm -2 were 50 and 228 mV, respectively.
[0032] The specific test steps for HER / OER are as follows: Electrochemical measurements of HER, OER, and OWS were performed using a 760E electrochemical workstation (Zhenhua, Shanghai, China) in a 1 M KOH electrolyte using a typical three-electrode electrochemical cell. The working electrode was 5.9% NiOOH / NiCu or the comparative material, the counter electrode was a carbon rod, and the reference electrode was Hg|HgO|OH-. Before the electrochemical test, the electrolyte was purged with argon to remove O2. In this study, all potentials were calculated relative to the reversible hydrogen electrode (RHE), where ERHE = E(vs. Hg|HgO|OH - ) + 0.059pH + 0.098. E(vs. Hg|HgO|OH - ) represents the experimental potential measured relative to the Hg / HgO reference electrode, and 0.241 V is the standard potential of Hg / HgO at 25 °C.
[0033] Example 2: (1) Prepare a mixed solution of 0.001 M ammonium persulfate and 0.025 M sodium hydroxide and mix well. (2) Immerse a piece of copper foam into the mixed solution obtained in (1) and carry out an in-situ oxidation reaction at 80 °C for 20 minutes to obtain a nanoarray CuO2 support (CuO2 array width = 2 µm). (3) Dissolve 3 mmol nickel sulfate hexahydrate, 2 mmol copper sulfate pentahydrate, and 0.35 g ammonium sulfate in 100 ml deionized water and mix well to form an electrodeposition mixed solution. (4) The obtained nanoarray CuO₂ support in (2) was immersed in the electrodeposition mixed solution obtained in (3). The ambient temperature was 25 °C and the ambient pressure was 0.1 MPa. The counter electrode was a graphite rod, the working electrode was the support, and the reference electrode was an Ag / AgCl electrode. Electrodeposition was carried out at a constant cathodic current of -0.2 A for 900 s; (5) The deposited transition metal catalyst was collected and washed clean with deionized water to obtain a 1.5% NiOOH / NiCu catalyst.
[0034] The lattice strain ratio was compared with the lattice width of the 0% material, and the calculation formula was:
[0035] where is the lattice spacing of the doped sample, and a is the lattice spacing of 0% NiOOH / NiCu.
[0036] (6) The prepared 1.5% NiOOH / NiCu catalyst was electrocatalytically tested for HER and OER in the presence of 1 M KOH to measure its activity. It was found that the HER and OER overpotentials at 10 mA·cm -2 were 40 and 216 mV, respectively.
[0037] Example 3: (1) A mixed solution of 0.01 M ammonium persulfate and 0.25 M sodium hydroxide was prepared and mixed well; (2) A piece of copper foam was immersed in the mixed solution obtained in (1), and an in-situ oxidation reaction was carried out at 80 °C for 20 minutes to obtain a nanoarray CuO₁ support (CuO array width = 1 µm); (3) 3 mmol of nickel sulfate hexahydrate, 2 mmol of copper sulfate pentahydrate and 0.35 g of ammonium sulfate were dissolved in 100 ml of deionized water and mixed well to form an electrodeposition mixed solution; (4) The obtained nanoarray CuO₁ support in (2) was immersed in the electrodeposition mixed solution obtained in (3). The counter electrode was a graphite rod, the working electrode was the support, and the reference electrode was an Ag / AgCl electrode. Electrodeposition was carried out at a constant cathodic current of -0.2 A for 900 s; (5) The deposited transition metal catalyst was collected and washed clean with deionized water to obtain a 3.4% NiOOH / NiCu catalyst.
[0038] (6) The prepared 3.4% NiOOH / NiCu catalyst was electrocatalytically tested for HER and OER in the presence of 1 M KOH to measure its activity. It was found that at 10 mA cm -2The HER and OER overpotentials are 37 and 212 mV, respectively, under the following conditions.
[0039] Example 4: (1) Prepare a mixed solution of 0.1 M ammonium persulfate and 2.5 M sodium hydroxide, and mix well. (2) Immerse a piece of copper foam into the mixed solution obtained in (1), and perform an in-situ oxidation reaction at 80 °C for 20 minutes to obtain a nanoarray CuO 0.1 support (CuO array width = 0.1 µm); (3) Dissolve 3 mmol of nickel sulfate hexahydrate, 2 mmol of copper sulfate pentahydrate, and 0.35 g of ammonium sulfate in 100 ml of deionized water, and mix well to form an electrodeposition mixed solution. (4) Use the nanoarray CuO 0.1 support obtained in (2) as the substrate, immerse it into the electrodeposition mixed solution obtained in (3), use a graphite rod as the counter electrode, the substrate as the working electrode, and an Ag / AgCl electrode as the reference electrode, and perform electrodeposition at a constant cathodic current of -0.2 A for 900 s. (5) Collect the transition metal catalyst after electrodeposition, wash it clean with deionized water to obtain a 5.9% NiOOH / NiCu catalyst (Ni3Cu2-CF).
[0040] (6) Electrocatalytic HER and OER of the prepared 5.9% NiOOH / NiCu catalyst were carried out in the presence of 1 M KOH to measure its activity, and it was found that the HER and OER overpotentials at 10 mA cm -2 are 18 and 198 mV, respectively.
[0041] Example 5: (1) Prepare a mixed solution of 0.2 M ammonium persulfate and 5 M sodium hydroxide, and mix well. (2) Immerse a piece of copper foam into the mixed solution obtained in (1), and perform an in-situ oxidation reaction at 80 °C for 20 minutes to obtain a nanoarray CuO 0.05 support (CuO array width = 0.05 µm); (3) Dissolve 3 mmol of nickel sulfate hexahydrate, 2 mmol of copper sulfate pentahydrate, and 0.35 g of ammonium sulfate in 100 ml of deionized water, and mix well to form an electrodeposition mixed solution. (4) Use the nanoarray CuO 0.05 support obtained in (2) as the substrate, immerse it into the electrodeposition mixed solution obtained in (3), use a graphite rod as the counter electrode, the substrate as the working electrode, and an Ag / AgCl electrode as the reference electrode, and perform electrodeposition at a constant cathodic current of -0.2 A for 900 s. (5) The electroplated transition metal catalyst was collected and washed thoroughly with deionized water to obtain the 8.6% NiOOH / NiCu catalyst.
[0042] (6) The as-prepared dendritic 8.6% NiOOH / NiCu catalyst was electrocatalytically tested for HER and OER activities in 1 M KOH, and the HER and OER overpotentials at 10 mA cm -2 were found to be 27 and 207 mV, respectively.
[0043] Comparative Example 1 (1) A mixed solution of 0.1 M ammonium persulfate and 2.5 M sodium hydroxide was prepared and mixed thoroughly. (2) A piece of copper foam (CF) was immersed in the mixed solution obtained in (1), and an in-situ oxidation reaction was carried out at 80 °C for 20 minutes to obtain the nanoarray CuO 0.1 support (CuO array width = 0.1 µm). (3) 5 mmol of nickel sulfate hexahydrate and 0.35 g of ammonium sulfate were dissolved in 100 ml of deionized water and mixed thoroughly to form an electroplating mixture. (4) Using the nanoarray CuO 0.1 support obtained in (2) as the substrate, it was immersed in the electroplating mixture obtained in (3). The counter electrode was a graphite rod, the working electrode was the substrate, and the reference electrode was an Ag / AgCl electrode. Electroplating was carried out at a constant cathodic current of -0.2 A for 900 s. (5) The electroplated transition metal catalyst was collected and washed thoroughly with deionized water to obtain the Ni5-CF catalyst with a stacked morphology.
[0044] (6) The as-prepared Ni5-CF catalyst was electrocatalytically tested for HER and OER activities in 1 M KOH, and the HER and OER overpotentials at 10 mA cm -2 were found to be 31 and 267 mV, respectively.
[0045] Comparative Example 2 (1) A solution of 0.1 M ammonium persulfate and 2.5 M sodium hydroxide was prepared and mixed thoroughly. (2) A piece of copper foam (CF) was immersed in the mixed solution obtained in (1), and an in-situ oxidation reaction was carried out at 80 °C for 20 minutes to obtain the nanoarray CuO 0.1 support (CuO array width = 0.1 µm). (3) 4.5 mmol of nickel sulfate hexahydrate, 0.5 mmol of copper sulfate pentahydrate and 0.35 g of ammonium sulfate were dissolved in 100 ml of deionized water and mixed thoroughly to form an electroplating mixture. (4) Using the nanoarray CuO obtained in (2) 0.1 as the substrate, immerse it into the electrodeposition mixed solution obtained in (3). Use a graphite rod as the counter electrode, the substrate as the working electrode, and an Ag / AgCl electrode as the reference electrode. Perform electrodeposition for 900 s at a constant cathodic current of -0.2 A. (5) Collect the transition metal catalyst after electrodeposition, wash it clean with deionized water to obtain a Ni 4.5 Cu 0.5 -CF catalyst with an initially obvious branch-like morphology.
[0046] (6) Perform electrocatalytic HER and OER on the prepared Ni 4.5 Cu 0.5 -CF catalyst in the presence of 1 M KOH to measure its activity. It is found that the HER and OER overpotentials at 10 mA cm -2 are 33 and 245 mV respectively.
[0047] Example 6 (1) Prepare a solution of 0.1 M ammonium persulfate and 2.5 M sodium hydroxide, and mix them thoroughly. (2) Immerse a piece of copper foam (CF) into the mixed solution obtained in (1), and perform an in-situ oxidation reaction at 80 °C for 20 minutes to obtain a nanoarray CuO 0.1 substrate (CuO array width = 0.1 µm). (3) Dissolve 4 mmol of nickel sulfate hexahydrate, 1 mmol of copper sulfate pentahydrate, and 0.35 g of ammonium sulfate in 100 ml of deionized water, and mix them thoroughly to form an electrodeposition mixed solution. (4) Using the nanoarray CuO obtained in (2) 0.1 as the substrate, immerse it into the electrodeposition mixed solution obtained in (3). Use a graphite rod as the counter electrode, the substrate as the working electrode, and an Ag / AgCl electrode as the reference electrode. Perform electrodeposition for 900 s at a constant cathodic current of -0.2 A. (5) Collect the transition metal catalyst after electrodeposition, wash it clean with deionized water to obtain a Ni4Cu1-CF catalyst with a clearer branch-like morphology.
[0048] (6) Perform electrocatalytic HER and OER on the prepared Ni4Cu1-CF catalyst in the presence of 1 M KOH to measure its activity. It is found that the HER and OER overpotentials at 10 mA cm -2 are 37 and 202 mV respectively.
[0049] Example 7 (1) Prepare a solution of 0.1 M ammonium persulfate and 2.5 M sodium hydroxide, and mix them thoroughly. (2) Immerse a piece of copper foam (CF) into the mixed solution obtained in (1), and conduct an in-situ oxidation reaction at 80 °C for 20 minutes to obtain a nanoarray CuO. 0.1 Support (CuO diameter = 0.1 µm); (3) Dissolve 2 mmol of nickel sulfate hexahydrate, 3 mmol of copper sulfate pentahydrate, and 0.35 g of ammonium sulfate in 100 ml of deionized water, and mix well to form an electrodeposition mixed solution; (4) Use the nanoarray CuO 0.1 obtained in (2) as the substrate and immerse it into the electrodeposition mixed solution obtained in (3). Use a graphite rod as the counter electrode, the substrate as the working electrode, and an Ag / AgCl electrode as the reference electrode, and perform electrodeposition at a constant cathodic current of -0.2 A for 900 s; (5) Collect the transition metal catalyst after electrodeposition, wash it clean with deionized water, and obtain a Ni2Cu3-CF catalyst with a relatively clear dendritic morphology.
[0050] (6) Electrocatalytic HER and OER of the prepared Ni2Cu3-CF catalyst were carried out in the presence of 1 M KOH to measure its activity, and it was found that the HER and OER overpotentials at 10 mA cm -2 were 43 and 221 mV, respectively.
[0051] Comparative Example 3 (1) Prepare a solution of 0.1 M ammonium persulfate and 2.5 M sodium hydroxide, and mix well; (2) Immerse a piece of copper foam (CF) into the mixed solution obtained in (1), and conduct an in-situ oxidation reaction at 80 °C for 20 minutes to obtain a nanoarray CuO 0.1 Support (CuO diameter = 0.1 µm); (3) Dissolve 1 mmol of nickel sulfate hexahydrate, 4 mmol of copper sulfate pentahydrate, and 0.35 g of ammonium sulfate in 100 ml of deionized water, and mix well to form an electrodeposition mixed solution; (4) Use the nanoarray CuO 0.1 obtained in (2) as the substrate and immerse it into the electrodeposition mixed solution obtained in (3). Use a graphite rod as the counter electrode, the substrate as the working electrode, and an Ag / AgCl electrode as the reference electrode, and perform electrodeposition at a constant cathodic current of -0.2 A for 900 s; (5) Collect the transition metal catalyst after electrodeposition, wash it clean with deionized water, and obtain a Ni1Cu4-CF catalyst with a relatively clear dendritic morphology.
[0052] (6) The prepared Ni1Cu4-CF catalyst was electrocatalytically tested for HER and OER in the presence of 1 M KOH to measure its activity, and it was found that the HER and OER overpotentials at 10 mA cm -2 were 51 and 241 mV, respectively.
[0053] Comparative Example 4 (1) Prepare a 0.1 M ammonium persulfate and 2.5 M sodium hydroxide solution and mix well; (2) Immerse a piece of copper foam (CF) into the mixed solution obtained in (1) and perform an in-situ oxidation reaction at 80 °C for 20 minutes to obtain a nanoarray CuO 0.1 support (CuO diameter = 0.1 µm); (3) Dissolve 5 mmol of copper sulfate pentahydrate and 0.35 g of ammonium sulfate in 100 ml of deionized water and mix well to form an electrodeposition mixed solution; (4) Using the nanoarray CuO 0.1 support obtained in (2) as the substrate, immerse it into the electrodeposition mixed solution obtained in (3). Use a graphite rod as the counter electrode, the substrate as the working electrode, and an Ag / AgCl electrode as the reference electrode, and perform electrodeposition at a constant cathodic current of -0.2 A for 900 s; (5) After the electrodeposition is completed, collect the transition metal catalyst, wash it clean with deionized water, and obtain a Cu5-CF catalyst composed of flakes with a clear branch morphology.
[0054] (6) The prepared Cu5-CF catalyst was electrocatalytically tested for HER and OER in the presence of 1 M KOH to measure its activity, and it was found that the HER and OER overpotentials at 10 mA cm -2 were 75 and 296 mV, respectively.
[0055] Comparative Example 5 This comparative example is basically the same as the steps of Example 4, except for the preparation of the copper oxide support.
[0056] Preparation of the copper oxide support: Prepare a mixed solution of 0.1 M ammonium persulfate and 2.5 M sodium hydroxide and mix well; Immerse a piece of copper foam in the mixed solution at room temperature (25 °C) for 20 minutes, then take out the copper foam, wash it clean and dry it to obtain Cu(OH)2 / Cu; Keep the dried Cu(OH)2 / Cu at 150 °C for 4 h to obtain a copper hydroxide support with a relatively disordered array morphology.
[0057] The prepared catalyst was electrocatalytically tested for HER and OER in the presence of 1 M KOH to measure its activity, and it was found that the HER and OER overpotentials at 10 mA·cm -2 were 137 and 339 mV, respectively.
[0058] Comparative Example 6 This comparative example is basically the same as the steps of Example 4, except that the preparation of the metal salt is different, and copper sulfate is replaced with cobalt sulfate in an equimolar amount.
[0059] The prepared catalyst was electrocatalytically tested for HER and OER in the presence of 1 M KOH to measure its activity, and it was found that the HER and OER overpotentials at 10 mA·cm -2 were 66 and 243 mV, respectively.
[0060] The CuO array morphology of the catalysts prepared in Examples 1 to 5 is as Figure 8 shown; the SEM images of the catalysts prepared in the examples and comparative examples are as Figure 1 , Figure 5 , Figure 9 shown; the HRTEM images are as Figure 2 shown, and the HER polarization curves are as Figure 3 , Figure 6 , Figure 10 shown; the OER polarization curves are as Figure 4 , Figure 7 , Figure 11 shown.
[0061] The HER and OER overpotential tests of the examples and comparative examples are shown in Table 1 below: Table 1
[0062] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various deformations or modifications within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A preparation method of a hydroxy-oxide and alloy-supported catalyst, characterized in that, It includes the following steps: S1. Dissolve an ammonium salt in an alkaline solution to obtain a mixed solution; then immerse the copper foam in the mixed solution and heat it to 50 - 120 °C for an in-situ oxidation reaction to obtain a nanoarray copper oxide support; S2. Mix and dissolve a transition metal salt, a copper salt, and an ammonium salt to obtain an electrodeposition mixed solution; S3. Use the obtained nanoarray copper oxide support as a working electrode, immerse it in the electrodeposition mixed solution, and perform electrodeposition to obtain a hydroxyoxide and alloy-supported catalyst.
2. The preparation method of the hydroxyoxide and alloy-supported catalyst according to claim 1, characterized in that, In step S1, the ammonium salt includes one or more of ammonium persulfate, ammonium chloride, ammonium bicarbonate, and ammonium nitrate; and / or, the molar concentration of the ammonium salt in the mixed solution is 0.001 - 0.4 M.
3. The preparation method of the hydroxyoxide and alloy-supported catalyst according to claim 1, characterized in that, In step S1, the alkaline solution includes one or more of sodium hydroxide solution, potassium hydroxide solution, and ammonia water solution; and / or, the molar concentration of the base in the mixed solution is 0.025 - 5 M.
4. The preparation method of the hydroxyoxide and alloy-supported catalyst according to claim 1, characterized in that, In step S1, the time of the in-situ oxidation reaction is 5 - 60 min.
5. The preparation method of the hydroxyoxide and alloy-supported catalyst according to claim 1, wherein, In step S1, the surface of the obtained nanoarray copper oxide support has a CuO array, and the array width is 0.05 - 2 µm.
6. The preparation method of the hydroxyoxide and alloy-supported catalyst according to claim 1, characterized in that, In step S2, the transition metal salt includes a sulfate; the transition metal includes one or more of nickel, cobalt, iron, and manganese; and / or, the copper salt includes one of copper sulfate and copper chloride; and / or, the proportion of the copper salt in the total molar amount of the transition metal salt and the copper salt is 20 - 60%.
7. The preparation method of the hydroxyoxide and alloy-supported catalyst according to claim 1, wherein In step S2, the ammonium salt includes one or more of ammonium sulfate, ammonium chloride, ammonium bicarbonate, and ammonium nitrate; and / or, in the electrodeposition mixed solution, the concentration of the ammonium salt is 0.05 - 0.5 g / 100 mL.
8. The preparation method of the hydroxyoxide and alloy-supported catalyst according to claim 1, wherein, In step S3, during electrodeposition, the ambient temperature is 20 - 30 °C, and the ambient pressure is 0.1 - 1 MPa; and / or, the range of the cathode constant current is -0.05 A to -0.2 A, and the deposition time is 300 - 1200 s; and / or, during electrodeposition, a graphite rod is used as the counter electrode, the working electrode is the deposition substrate, and the reference electrode is an Ag / AgCl electrode, and electrodeposition is carried out in a cathode constant current mode.
9. The preparation method of the hydroxyoxide and alloy-supported catalyst according to claim 1, wherein, The hydroxyoxide and alloy-supported catalyst obtained in step S3 has a three-dimensional hierarchical branch-leaf structure, which includes an alloy branch structure and a hydroxyoxide leaf structure. The size of the branch structure is 50 - 300 nm, and the average thickness of the leaf structure is 1.4 - 1.6 nm.
10. Application of a hydroxyoxide and alloy-supported catalyst obtained by the preparation method as claimed in claim 1 in electrocatalytic overall water splitting for hydrogen evolution and oxygen evolution.
Citation Information
Cited By
Method for synthesizing NiFeCu array catalyst by template method and NiFeCu array catalyst
CN120519884A